Influence Factors for Community-Based Road Quality in Slum Settlement Areas - Mochammad Reyhan Firlandy; Hitapriya Suprayitno; Eko Budi Santoso; Tri Joko Wahyu Adi (Journal of Infrastructure & Facility Asset Management, 2020)
National Long-Term Development Plan (RPJPN) mandated to alleviate slum settlement areas until 0 hectares. One of the indicators to be assessed on slum settlement handling is by road settlement access. The quality of the road was affected by the physical condition and the operation, management factors either. This research aim is to identify factors that affected community-based settlement road management in slum settlement areas, through Kota Tanpa Kumuh (KOTAKU) Program or City Without Slum. The analysis used in this research is descriptive analysis, in which the researcher gathers factors related to community-based road management from literature study, also previous study and research. Then 7 experts that have expertise in slum alleviation subjects were chosen, to validate and filter the factors that have been gathered. The results indicate that there are 25 approved factors by all experts and considered as high influence factors, 13 factors approved by 4 - 6experts considered as moderate influence factors, and 3 factors approved by less than 4 experts considered as low influence factors. This research contributes to Infrastructure Asset Management knowledge, specificallyin community-based infrastructure management.